FACTORS AFFECTING THE COMPLIANCE OF SUSTAINABLE RICE PRODUCTION IN THE MEKONG DELTA, VIETNAM - Le Canh DUNG; Vo Van TUAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study aims to determine the factors affecting compliance with Sustainable Rice Platform (SRP) standards in rice production in the Mekong Delta, which is considered the largest rice granary in Vietnam and is of great importance in the world rice export market. The study was conducted based on survey data for 426 rice-growing households and implementing SRP standards in the region by 2022. The study results showed that only 6.57% of rice-growing households could fully comply the SRP standard, while the majority of households encountered certain obstacles. The analysis results from the binary regression show that some factors that positively affect the compliance with SRP standards are the education level of the household head, the size of rice land and contract farming. Meanwhile, large demographic size has a negative effect on compliance with SRP standards. In addition, infrastructure factors such as intra-field road condition and post-harvest straw collection services are community-level constraints affecting compliance with SRP standards. Based on the results of this study, some solutions and policy implications are proposed.